Evaluation of Service learning in ICT curriculum - Mikelić Preradović, Nives; Boras, Damir; Kišiček, Sanja (2010)
Theoretical knowledge without (practical) skills and weak connection between university education and labour market needs are two most important educational issues facing higher education in Croatia today. Higher education in Croatia lacks emphasis on the integration of theory and social needs. Service learning (SL) is a teaching strategy that connects meaningful community service with academic learning and civic responsibility. SL was introduced into Information Science curriculum at the Faculty of Humanities and Social Sciences in Zagreb for the first time in 2006/07, with the goal to transform the old teaching style. This study examined the quality of 40 SL projects using Youth Service California's Service Learning Quadrant (2000). The results showed that SL can become a useful academic tool in transforming our Department and Faculty into a place that meets the needs of the new economic reality of changing markets and rapidly developing technology.
Projekt MZOS
Projekt MZOS
ENG